Polyethylenimine-Conjugated Au-NPs as an Efficient Vehicle for in vitro and in vivo DNA Vaccine Delivery - Kartouzian A; Heiz A; Shameli K; Moeini H (International Journal of Nanomedicine)
Aras Kartouzian,1 Alexandra Heiz,1 Kamyar Shameli,2,* Hassan Moeini3,* 1Catalysis Research Center, School of Natural Sciences, Technical University of Munich, Munich, Germany; 2Institute of Virology, School of Medicine, Technical University of Munich, Munich, Germany; 3Iguana Biotechnology GmbH, Munich, Germany*These authors contributed equally to this workCorrespondence: Kamyar Shameli; Hassan Moeini, Email kamyarshameli@gmail.com; moeini82@yahoo.comPurpose: This study aimed to develop green-synthesized gold nanoparticles (Au-NPs) conjugated with polyethyleneimine (PEI) to overcome challenges in intracellular DNA vaccine delivery, focusing on enhancing cellular uptake and immune responses against the human norovirus (HuNoV) GII.4 variants.Methods: Au-NPs were synthesized using a citrate-ion-mediated green approach, with size and morphology analyzed via UV-vis spectroscopy and transmission electron microscopy (TEM). Stability was evaluated through zeta potential measurements. PEI conjugation was employed to modify surface charge. After in vitro evaluation of pDNA delivery efficiency and cytotoxicity in HEK293 cells, PEI-coated Au-NPs loaded with a HuNoV GII.4 pDNA vaccine (AuPEI-NPs-pDNA) were assessed for the immune responses in mice.Results: UV-vis spectroscopy and TEM confirmed successful Au-NP synthesis. Zeta potential shifted from − 31.38 mV to − 20.60 mV, reflecting stable but slightly reduced colloidal stability with larger sizes. PEI conjugation reversed surface charge to positive, enabling 100% transfection efficacy in HEK293 cells by day two without cytotoxicity. The AuPEI-NPs-pDNA induced significantly higher NoV-specific IgG antibodies and T-cell responses compared to unmodified Au-NPs, highlighting the role of positive charge in enhancing cellular uptake and immune activation. These results underscore PEI-coated Au-NPs as a biocompatible, efficient platform for DNA vaccine delivery.Conclusion: PEI-coated Au-NPs demonstrate exceptional potential as non-toxic, high-efficiency carriers for DNA vaccines, enabling robust humoral and cellular immune responses. This strategy holds promises for advancing gene therapy and combating rapidly evolving pathogens like HuNoV, with broader applications in targeted drug delivery.Keywords: gold nanoparticle, polyethylenimine, DNA vaccine, gene delivery, in vitro, in vivo